Cutis 2020
DOI: 10.12788/cutis.0011
|View full text |Cite
|
Sign up to set email alerts
|

Anti–PD1 Immune Checkpoint Inhibitor–Induced Bullous Pemphigoid in Metastatic Melanoma and Non–Small Cell Lung Cancer

Abstract: Anti-programmed cell death 1 (PD1) targeted immune checkpoint inhibitors such as nivolumab and pembrolizumab are increasingly used to treat advanced malignancies such as melanoma, non-small cell lung cancer, urothelial cancer, and renal cell carcinoma. A rare but increasingly reported adverse effect of anti-PD1 therapy is bullous pemphigoid (BP), an autoimmune blistering disease directed against BP antigen 1 and BP antigen 2 in the basement membrane of the epidermis. We present 3 cases of BP secondary to anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The overall incidence of bullous dermatoses with anti‐PD‐1/anti‐PD‐L1 agents is estimated about 1%, 59 whereas the reported incidence for anti‐PD‐L1 agents alone ranges from 1.3% to 5%, raising concerns of a higher risk with the use of the latter 68 . Lichen planus pemphigoides, pemphigus, dermatitis herpetiformis, linear IgA bullous dermatosis or mucous membrane pemphigoid have been much more rarely reported in association with ICIs 59,67,69–74 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall incidence of bullous dermatoses with anti‐PD‐1/anti‐PD‐L1 agents is estimated about 1%, 59 whereas the reported incidence for anti‐PD‐L1 agents alone ranges from 1.3% to 5%, raising concerns of a higher risk with the use of the latter 68 . Lichen planus pemphigoides, pemphigus, dermatitis herpetiformis, linear IgA bullous dermatosis or mucous membrane pemphigoid have been much more rarely reported in association with ICIs 59,67,69–74 …”
Section: Methodsmentioning
confidence: 99%
“…68 Lichen planus pemphigoides, pemphigus, dermatitis herpetiformis, linear IgA bullous dermatosis or mucous membrane pemphigoid have been much more rarely reported in association with ICIs. 59,67,[69][70][71][72][73][74] Pathogenesis of ICI-induced BP is vague, but it more likely represents a secondary consequence of both B-and T-cell activation in the context of immune stimulation. PD-1 inhibition may activate antibody-secreting B cells and inhibit immunosuppressive B regulatory cells.…”
Section: Autoimmune Bullous Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also found renal cell carcinoma to be associated with BP following PD‐1 therapy. Additionally, two 70‐year‐old patients with stage IV melanoma and lung metastases developed BP between 9 and 12 months following the usage of PD‐1 inhibitors 11 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two 70-year-old patients with stage IV melanoma and lung metastases developed BP between 9 and 12 months following the usage of PD-1 inhibitors. 11 Unlike other dermatologic irAEs which occur early in treatment, immunotherapy-induced bullous dermatoses demonstrate latency beyond the first treatment cycle. Often, mild and localized pruritus is the only clinical symptom before quickly progressing to hemorrhagic blisters on the chest, abdomen, thighs, and upper arms.…”
Section: Bp In Association With Pd-1 Inhibitor Therapymentioning
confidence: 99%